Google-Translate-Combined Emotion Analysis in Translating Literary Works: Comparison of Two Chinese Versions of David Copperfield - Li, Yan (Intercultural Communication Studies, 2026)
Google-Translate-Combined Emotion Analysis in Translating Literary Works: Comparison of Two Chinese Versions of David Copperfield